Analysis of two D1-like dopamine receptors from the honey bee Apis mellifera reveals agonist-independent activity - Mustard, Julie A.; Blenau, Wolfgang; Hamilton, Ingrid S.; Ward, Vernon K.; Ebert, Paul R.; Mercer, Alison R. (Brain research. Molecular brain research., 2003)
Dopamine is found in many invertebrate organisms, including insects, however, the mechanisms through which this amine operates remain unclear. We have expressed two dopamine receptors cloned from honey bee ( AmDOP1 and AmDOP2) in insect cells ( Spodoptera frugiperda), and compared their pharmacology directly using production of cAMP as a functional assay. In each assay, AmDOP1 receptors required lower concentrations of dopamine and 6,7-ADTN for maximal activation than AmDOP2 receptors. Conversely, butaclamol and cis( Z)-flupentixol were more potent at blocking the cAMP response mediated through AmDOP2 than AmDOP1 receptors. Expression of AmDOP1, but not AmDOP2, receptors significantly increased levels of cAMP even in the absence of ligand. This constitutive activity was blocked by cis( Z)-flupentixol. This work provides the first evidence of a constitutively activated dopamine receptor in invertebrates and suggests that although AmDOP1 and AmDOP2 share much less homology than their vertebrate counterparts, they display a number of functional parallels with the mammalian D1-like dopamine receptors.